2010
DOI: 10.1177/0733464810372771
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Users and Nonusers of Day Care Centers Among Frail Older Persons in Israel

Abstract: Day care centers are one of the core community-based services for frail older persons. The purpose of the study is to examine differences in characteristics of users and nonusers of day care centers among frail older people and factors that explain service utilization. Personal interviews are conducted with 333 respondents, of whom 81 were users. Based on the behavioral model of Andersen, the results show that both groups significantly differed in most predisposing (age, marital status), enabling (having a hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Varying levels of social support outside day centres were reported in five studies (Del Aguila, Cox and Lee 2006, Fulbright 2010, Iecovich and Carmel 2011, Chaichanawirote and Higgins 2013, Wittich, Murphy and Mulrooney 2014). Having an inadequate informal network was one of two factors found to contribute to the decision to apply for a day centre place (Del Aguila, Cox and Lee 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Varying levels of social support outside day centres were reported in five studies (Del Aguila, Cox and Lee 2006, Fulbright 2010, Iecovich and Carmel 2011, Chaichanawirote and Higgins 2013, Wittich, Murphy and Mulrooney 2014). Having an inadequate informal network was one of two factors found to contribute to the decision to apply for a day centre place (Del Aguila, Cox and Lee 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a large amount of literature has been devoted to the determinants of senior center attendance [28,29] and some studies have reported female seniors to use these centers more often than male seniors [7,30], while others have found no significant relationship between gender and senior center attendance [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Andersen’s Behavioral Model of Health Services Use (ABM) is widely used in studies on health service utilization. 20-30 It provides a framework for describing and understanding individuals’ decision to use health care services. We consider the dependent variables in this study, contracted with GP services and willingness to contract, as health care utilization, which is similar to other published studies.…”
Section: Introductionmentioning
confidence: 99%